The Impact of Basal Roughness on Inland Thwaites Glacier Sliding - Andrew O. Hoffman; Knut Christianson; Nicholas Holschuh; Elizabeth Case; Jonathan Kingslake; Robert Arthern (Geophysical Research Letters)
Abstract Swath radar technology enables three‐dimensional mapping of modern glacier beds over large areas at resolutions that are higher than those typically used in ice‐flow models. These data may enable new understanding of processes at the ice‐bed interface. Here, we use two densely surveyed swath‐mapped topographies (<50 m2 resolution) of Thwaites Glacier to investigate the sensitivity of inferred basal friction proxies to bed roughness magnitude and orientation. Our work suggests that along‐flow roughness influences inferred friction more than transverse‐flow roughness, which agrees with analytic form‐drag sliding theory. Using our model results, we calculate the slip length (the ratio of internal shear to basal slip). We find excellent agreement between the numerically derived slip lengths and slip lengths predicted by analytic form‐drag sliding theory, which suggests that unresolved short wavelength bed roughness may control sliding in the Thwaites interior.